2012
DOI: 10.1093/cercor/bhs068
|View full text |Cite
|
Sign up to set email alerts
|

Boosting Human Learning by Hypnosis

Abstract: Human learning and memory depend on multiple cognitive systems related to dissociable brain structures. These systems interact not only in cooperative but also sometimes competitive ways in optimizing performance. Previous studies showed that manipulations reducing the engagement of frontal lobe-mediated explicit attentional processes could lead to improved performance in striatum-related procedural learning. In our study, hypnosis was used as a tool to reduce the competition between these 2 systems. We compar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

7
105
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 98 publications
(113 citation statements)
references
References 41 publications
7
105
1
Order By: Relevance
“…It is still debated if relationship exists between short-term memory (STM), executive functions and implicit sequence/statistical learning Nemeth, 2013, 2015;Martini et al, 2014), and if does then what its direction is. Several studies claim a competitive relationship between frontal lobe-related control/executive functions and implicit learning (Filoteo et al, 2010;Nemeth et al, 2013;Poldrack et al, 2001;Poldrack and Packard, 2003), and consequently, negative correlation was found between executive functions and implicit statistical learning Virag et al, 2015). Future studies should directly focus on these potential associations in BPD with a larger sample size.…”
Section: Discussionmentioning
confidence: 93%
“…It is still debated if relationship exists between short-term memory (STM), executive functions and implicit sequence/statistical learning Nemeth, 2013, 2015;Martini et al, 2014), and if does then what its direction is. Several studies claim a competitive relationship between frontal lobe-related control/executive functions and implicit learning (Filoteo et al, 2010;Nemeth et al, 2013;Poldrack et al, 2001;Poldrack and Packard, 2003), and consequently, negative correlation was found between executive functions and implicit statistical learning Virag et al, 2015). Future studies should directly focus on these potential associations in BPD with a larger sample size.…”
Section: Discussionmentioning
confidence: 93%
“…A recent study provides further compelling evidence of frontal inhibition under hypnosis (Nemeth, Janacsek, Polner, & Kovacs, 2013). Nemeth et al showed that implicit, procedural learning is improved under hypnosis.…”
Section: Frontal Executive Functions and Hypnosismentioning
confidence: 96%
“…Although some studies have suggested that implicit sequence learning can proceed with little or no use of attentional resources (Cleeremans & Jiménez, 1998;Frensch, Lin, & Buchner, 1998), other studies have shown impaired implicit learning when attention is diverted away from the primary implicit-learning task (Shanks & Channon, 2002;Shanks, Rowland, & Ranger, 2005). Still other results support the view that inattention may actually improve implicit learning (Filoteo, Lauritzen, & Maddox, 2010;Nemeth, Janacsek, Polner, & Kovacs, 2013; though see Newell, Moore, Willis, & Milton, 2013, for a reevaluation of Filoteo et al, 2010).…”
mentioning
confidence: 99%